APLIKASI RIZOBAKTERI SEBAGI BIOSTIMULAN PADA PERTUMBUHAN TANAMAN PADI (Oryza Sativa L.) - Iswanto Iswanto; Adrianus Adrianus; Diana S Susanti; Mariana L Resubun (Musamus University, 2022)
ABSTRACT The objective of this study is to find out the ability of rhizobacteria as a biostimulant in increasing the growth of rice plants as well as to get the right type of Rhizobacteria for rice plant growth this research was conducted in October 2020 until January 2021 at the agrotechnology laboratory end screen house of the faculty of agriculture, musamus university this study used a Randomized Design Group (RAK) consisting of four treatments end one control, Providencia vermicular, Myroides Adoratimimus, Serratia marcescent, Myrodes ordoratimus, The treatment was repeated 5 times so that 25 pots of experiments were obtained The treatment of rhizobacteria affects, plant height, rice root lengh end dry weight of roots. But it has no real effect on, the number of tillers, the number of panicles, and productive tillers. Rhizobacteria treatment is best for rice plant growth (Oryza sativa L).is Providencia vermiicoala.In Duncan’s Multiple Range (DMRT) test at 5% Keywords : rhizobacteria growth, Oryza Sativa L.